PENGARUH RESPONSIBILITAS PROFESI, MOTIVASI PERPRESTASI, DAN PENGETAHUAN MATERI AJAR TERHADAP KOMITMEN ORGANISASIONAL GURU SMAN DI DKI JAKARTA - NUROCHIM, NUROCHIM (Jurnal Ilmiah Educational Management, 2015)
The objective of this research is to study comprehensively the effect of responsibility profession, knowledge of economics material learning, and achievement motivation on organizational commitment. The research was conducted at State Senior High School Jakarta, and 57 samples were selected by using simple random sampling. The data were collected, by using questionnaires concerning four variables, and they are were analyzed in Path Analysis. The data analysis indicates that (1) organizational commitment was directly affected by responsibility profession, (2) organizational commitment was directly affected by knowledge of economics material learning, (3) organizational commitment was directly affected by achievement motivation, (4) achievement motivation was directly affected by responsibility profession, (5) achievement votivation was directly affected by knowledge of economics material learning. The result lead to recommendation, all of education authorities, the management of school, and especially economics teacher to give full support to increase responsibility profession, knowledge of economics material learning, and achievement motivation.